Analysis of the Effect of Activity Based Costing on Financial Performance - Sundari, Sri; Kurniawan, Awi; Wahid, Abdul; Syamsuddin, Syamsuddin (Jurnal Manajemen Bisnis, Akuntansi dan Keuangan, 2024)
This study examines the impact of Activity-Based Costing (ABC) on corporate financial performance, focusing on its ability to improve cost management in a competitive global market. ABC allocates overhead costs more accurately by identifying activities driving expenses, enabling better decision-making and operational efficiency. The research utilizes a literature review to analyze studies on ABC’s implementation across various industries, with data gathered from academic journals, books, and other relevant sources. The findings show that ABC positively influences financial performance by enhancing cost control, operational efficiency, and profitability. It provides valuable insights for strategic decisions such as pricing and resource allocation. However, challenges such as high implementation costs and the need for organizational change may impede adoption. Despite these barriers, the benefits of ABC, including improved competitiveness and profitability, outweigh the costs.